2015
DOI: 10.3389/fpubh.2015.00017
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers’ Perceptions and Self-Reported Fall Prevention Practices: Findings from a Large New York Health System

Abstract: Among older adults, falls are the leading cause of injury-related deaths and emergency department visits, and the incidence of falls in the United States is rising as the number of older Americans increases. Research has shown that falls can be reduced by modifying fall-risk factors using multifactorial interventions implemented in clinical settings. However, the literature indicates that many providers feel that they do not know how to conduct fall-risk assessments or do not have adequate knowledge about fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Only 8% of respondents reported fall prevention practices based on guidelines from recognized organizations; lack of time, more pressing medical problems and lack of educational materials were the most frequently cited barriers to fall risk assessment [ 18 ]. Among 38 healthcare providers from 11 New York state practices, Smith et al found that less than 40% asked most or all their older adult patients if they had fallen in the last year; less than 20% referred their older patients to community-based fall prevention programs; and, less than 16% conducted standardized functional assessment with their older patients at least once a year [ 19 ]. Burns et al analyzed data on fall prevention recommendations to older adult patients among 1210 US primary care providers who participated in the 2014 DocStyles survey [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only 8% of respondents reported fall prevention practices based on guidelines from recognized organizations; lack of time, more pressing medical problems and lack of educational materials were the most frequently cited barriers to fall risk assessment [ 18 ]. Among 38 healthcare providers from 11 New York state practices, Smith et al found that less than 40% asked most or all their older adult patients if they had fallen in the last year; less than 20% referred their older patients to community-based fall prevention programs; and, less than 16% conducted standardized functional assessment with their older patients at least once a year [ 19 ]. Burns et al analyzed data on fall prevention recommendations to older adult patients among 1210 US primary care providers who participated in the 2014 DocStyles survey [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…CDC has recognized a need to increase awareness among primary care physicians to conduct comprehensive medication review as part of the fall-risk assessment in the elderly. 34 This medication review should include an evaluation of number of medications and screening for PIMs, eliminating of potential therapeutic duplications, and screening for drug–drug interactions. 35 …”
Section: Discussionmentioning
confidence: 99%
“…In one study, AHPs believed GPs did not view them as important contributors to patient care in fall prevention, and believed GPs were too busy to make or receive phone calls . Research in the United States found less than a quarter of doctors, nurses and specialty care providers referred older adults for gait or balance training and less than a fifth referred to community‐based programs . The reasons given for low referral include doctors not being aware of how other health professionals can contribute to fall prevention; not knowing how to refer; not knowing eligibility criteria for home safety assessments or community programs; and not having time to refer …”
Section: Introductionmentioning
confidence: 99%
“…7 Research in the United States found less than a quarter of doctors, nurses and specialty care providers referred older adults for gait or balance training and less than a fifth referred to communitybased programs. 8 The reasons given for low referral include doctors not being aware of how other health professionals can contribute to fall prevention 9 ; not knowing how to refer; not knowing eligibility criteria for home safety assessments or community programs; and not having time to refer. 10,11 The Integrated Solutions for Sustainable Fall Prevention (iSOLVE) project engaged with GPs and AHPs in metropolitan Sydney to embed integrated evidence-based processes for identifying and managing older people at risk of falls.…”
Section: Introductionmentioning
confidence: 99%